Speech Act Features of Select Extracts in Chinua Achebe’s Arrow of God: Leadership Perspective - Akinkurolere, Susan Olajoke; Ariyo, Kayode Samuel (British Journal of Education, Society & Behavioural Science, 2015)
This paper examines the speech act features of select extracts of Chinua Achebe’s Arrow of God by examining the pragmatic implications of the speech acts employed and their relevance for promoting leadership in the contemporary society as it has been observed that the century has witnessed a great deal of leadership crisis especially in Nigeria. This paper is of the opinion that the use of appropriate speech acts through the various avenues opened up by language could beam light against the backdrop of the seemingly intractable socio-political conflicts that are prevalent across the globe. The exploration of certain portions of Arrow of God is a call for appropriate acts in the socio-political sphere in Nigeria and all over world. This study concludes that the effective acts in the communication of the leaders in government could enhance good governance through the investigation of the speech act choices and the perlocutionary effects in Chinua Achebe’s Arrow of God..
Keywords: Literature; Pragmatics; Language; Speech acts